Aspiration: /aspə'rāSH(ə)n. Issue 5 (September 2018) - Ferguson, John; Ravert, Brian; Gailey, Michael
Abstract : Aspiration is a mechanism in which liquid or solid penetrates into the lungs, which overlaps several disease states. Use of the terms aspiration and aspiration pneumonia is ambiguous and may include pulmonary infection, oropharyngeal dysphagia, or gastroesophageal reflux disease. This article reviews the literature and classifies 13 distinct syndromes, grouped into 3 categories to help delineate the different disease states associated with pulmonary aspiration. Chronic anaerobic pulmonary infection should be most precisely referred to as anaerobic pneumonia. The commonly used term, aspiration pneumonia, is misleading to clinicians and should be abandoned.